Bioefficacy of different insecticides against aphid in cumin - Dangi, N L; Mahla, M K; Ahir, K C; Swami, Hemant (Indian Journal of Plant Protection, 2020)
An experiment was conducted in randomized block design at KVK Bhilwara, Maharana Pratap University of Agriculture and Technology, Udaipur to evaluate the efficacy of carbosulfan 25% EC at 250, 312.5 and 375 g a.i./ ha in comparison thiamethoxam 25% WG at 25 g a.i./ha, imidacloprid 17.8 SL at 25 g a.i./ha and acetamiprid 20% SP at 10 g a.i./ha against aphid (Myzus persicae) in cumin during Rabi, 2013-14 and 2014-15. The results revealed that two sprays of carbosulfan 25% EC at 375 g a.i./ha were effective against aphid. It caused maximum mean reduction in aphid population after second spray at 10 days after application, which was 87.52 and 88.45 per cent during 2013-14 and 2014-15, respectively. It was followed by carbosulfan 25% EC at 312.5 g a.i./ha. The highest yields were recorded in case of carbosulfan 25% EC at 375 g a.i./ha, which were 622.3 and 456.7 kg/ha during 2013-14 and 2014-15, respectively and incremental yield of 358.6 kg/ha over untreated control.